Five Faces of Citational Injustice: Applying the Work of Iris Marion Young - Popowich, Sam (KULA)

(untitled) (University of Victoria Libraries, 2026)
This article explores the non-distributive conception of justice found in the work of feminist political philosopher Iris Marion Young (1949–2006), particularly in her landmark volume Justice and the Politics of Difference (1990). As laid out in that work, Young’s “five faces of oppression”—exploitation, marginalization, powerlessness, cultural imperialism, and violence—are central to the issues posed by citational justice scholarship and open up new ways of understanding how citational injustice is unjust. By connecting Young’s work with questions of citational justice, this article seeks to develop a nuanced conception of injustice as oppression, and thus as a matter of radical progressive politics, rather than merely a question of the (re)distribution of goods, which is too easily coopted to the capitalist logics of the corporatized university. The article concludes with some thoughts around reading and generative AI in academic work.